AB0729 Baseline Levels of CTX-II and Glucosyl-Galactosyl-Pyridinoline in Patients Wih Early Psoriasic Arthritis: Association with Disease Severity, Disability, Quality-of-Life, Biological Treatment Required and Progression of Joint Destruction at 5 Years of Follow Up. (15th July 2016) - Trujillo, E.; Garcia, M.; Sanchez, H.; Exposito, L.; Monroy, A.; Trujillo, M.D.M.
Abstract : Background: Although many efforts have been made to identify Psoriasic Arthritis (PsA)-specific biomarkers, none of the putative ones identified so far has resulted in a clinically relevant outcome and patient benefit. In other diseases of the joints, elevated levels of urinary CTX-II (C-telopeptide fragments of type II collagen) and Glc-Gal-PYD (glucosyl-galactosyl-pyridinoline) have been associated with progression of damage. Objectives: To analyze the association between the baseline levels of urinary CTX-II and Glc-Gal-PYD in patient with early PsA with disability, quality of life, biological treatment required and radiological damage at 5 years of follow up. Methods: We included 36 patients who came to the service with some of the suggestive information of PsA and who later completed five years of follow-up and they fulfill nowadays PsA according to classification of psoriatic arthritis (CASPAR) criteria. Urine samples were taken from all patients attending for the first time with suspected early PsA. Urinary excretion of CTX-II was determined by immunoassay (ELISA) (ng/ml). Urinary excretion of Glc-Gal-PYD was determined by High performance liquid chromatography (HPLC). Because urinary levels were not normally distributed, all data were transformed into logarithms for analysis. Association analysis was performed with the following five variables at 5 years: Disease Severity for the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA): mild, moderate and severe. Health Assessment Questionnaire (HAQ). Study Short Form 36 (SF-36). Anti-TNF therapy: Yes/No. Sharp-van Der Heijde modified scoring method for PsA. Results: Baseline levels of urinary excretion of CTX-II and Glc-Gal-PYD in patients presenting for the first time with suspected early SpA were significantly higher in those who had HAQ and SF-36 scores significantly worse, required biological treatment and in those due to moderate and severe disease severity at five years of follow up. In a multivariable linear regression analysis, Baseline levels of urinary excretion of CTX-II and Glc-Gal-PYD in patients presenting for the first time with suspected early SpA were an important predictor of worse radiological score at the age of 5 (erosions, joint space narrowing, (subluxation, ankylosis, gross osteolysis, and pencil in cup phenomena). Conclusions: Baseline levels of urinary excretion of CTX-II and Glc-Gal-PYD in patients with early SpA may be a prognostic biomarker since in our series it was associated with worse disease severity, disability, quality-of-life and progression of joint destruction at 5 years of follow up. Disclosure of Interest: None declared